Effect of chemical treatment on mechanical properties and water diffusion characteristics of jute‐polypropylene composites. Issue 4 (9th December 2019) - Chandekar, Harichandra; Chaudhari, Vikas; Waigaonkar, Sachin; Mascarenhas, Adlete
Abstract: This work presents the effect of chemical treatment of short jute fibers using alkali, potassium permanganate, and silane treatment on the mechanical properties of jute‐polypropylene (PP) composites. The chemically treated jute fibers were compounded at 30% weight fraction with PP granules in twin‐screw extruder, and the composite pellets were later injection molded to obtain the specimens for the study. The optimum parameters for the respective chemical treatments used in this study were followed as per the literature. The effectiveness of the chemical treatment carried out was studied using Fourier transform infrared spectroscopy and scanning electron microscopy. The mechanical characterization comprising tensile test, flexural test, impact test, and microhardness test were conducted on jute‐PP composites. In addition, the effect of chemical treatment on the water absorption kinetics of the jute‐PP composites was studied. The diffusion coefficient of the jute‐PP composite was determined using the approximate solution of Fick's model. The silane‐treated jute‐PP composites show an increase in tensile strength, tensile modulus, and flexural modulus by nearly 6%, 22%, and 20%, respectively, compared to untreated jute‐PP composite. The moisture absorption study reveals that the silane‐treated jute‐PP composite is the most effective.